English Teaching Materials for Teaching Recount Text: A Design and Students’ Reflection - hendriwanto, hendriwanto (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2018)
This study was aimed at designing the teaching materials for learning recount text as a type of genre in senior high school students. This study used Design Based Research method level one by researching without testing. The results obtained that students need the teaching material recount text written in accordance with students understanding, an attractive packaging and helping independent study. This study also obtained that the teaching material designed according to the students’ needs such as the arrangement of the colors, the image, and inscription on the front cover of the module to be placed in the appropriate position to make it look attractive. This study implies that teaching materials can be as facilitator to comprehend a wide range of genre types.